Sensory Processing Sensitivity and its association with personality traits and affect: A meta-analysis - Lionetti, Francesca; Pastore, Massimiliano; Moscardino, Ughetta; Nocentini, Annalaura; Pluess, Karen; Pluess, Michael (Journal of research in personality, 2019)
•Sensory Processing Sensitivity (SPS) is related but relatively distinct from common personality traits and affect.•SPS correlates positively with neuroticism in children and adults.•SPS correlates positively with openness in adults only.•SPS in children is moderately associated with both positive and negative affect.•SPS in adults is moderately associated with negative affect. In two Bayesian meta-analyses, we investigated associations between Sensory Processing Sensitivity (SPS) and the Big Five personality traits (MA1) as well as both Positive and Negative Affect (MA2). Moderators were age and the three SPS subscales. In MA1 (8 papers, 6790 subjects), SPS in children correlated with Neuroticism (r = 0.42) but did not with Extraversion, Openness, Agreeableness or Conscientiousness. In adults, SPS correlated with Openness (r = 0.14) and Neuroticism (r = 0.40) but did not with Extraversion, Agreeableness or Conscientiousness. In MA2 (19 papers, 5326 subjects), SPS in children correlated with Negative (r = 0.29) and Positive Affect (r = 0.21), but only with Negative Affect (r = 0.34) in adults. Developmental and measurement aspects are discussed.